EFFECT OF EXTRACT OF SEEDS OF Trigonella foenum-graecum L. AND VITAMIN C ON GROWTH AND YIEHD OF Vicia faba L. - Al-Kaisy, Wifak A.; Hilal, Hajer Mahammed (Diyala Agricultural Sciences Journal, 2013)
A biological experiment was conducted in botanical garden of Biology Department/Collage of Education (Ibn Al-Haitham), University of Baghdad during winter season of 2010-1011. The aim of the experiment was to study the effect of extract of seeds of two concentration 1% and 2% of fenugreek (Trigonella foenum-graecum) and also effect of vitamin C in two concentration 40 and 60 ppm on growth and yield of Vicia faba L. The results showed that the extract of seeds of fenugreek in 1% concentration increased, leaf area index 107.7%, chlorophyll content in leaves 13.4%, flowers number 183.8%, pods number 72.9%, weight of 100 grains 33.8%, the average weight of grain 51.5%, harvest index 34.2%, percentage of carbohydrate 22.6% and protein 45.9%. The vitamin C in 40 ppm increase of leaf area index 63.46%, chlorophyll content 12.7%, grains number in pod 25.3%, weight of 100 grains 23.2%, the average weight of grain 38.9% and percentage of carbohydrate and protein 21.6%, 54.3% respectively compared with control plants.